The challenge of Mediterranean sclerophyllous vegetation under climate change: From acclimation to adaptation - Bussotti, Filippo; Ferrini, Francesco; Pollastrini, Martina; Fini, Alessio (Environmental and Experimental Botany, 2014)
Forecasting models for climate change in southern Europe differ from those proposed for central and northern regions mainly with regard to precipitation. In fact, a strong reduction in average rainfall, mainly caused by decrease frequency of rainy events, is believe to occur in the Mediterranean basin in the forthcoming hundred years. Increased frequency of drought events will be paralleled and exacerbated by warming. Differently from areas where plant growth is limited by sub-optimal temperature (i.e. boreal and most temperate forests) and where warming has been reported to increase carbon assimilation and growth, plants growing in the Mediterranean basin are currently near their temperature optimum, and warming may contribute (e.g. with drought) to impair photosynthesis and depress growth and survival. Rising atmospheric CO2 has been found to increase growth, photosynthesis water use efficiency, and may partially alleviate the deleterious effects of warming and drought. However, in areas where severe and prolonged drought episodes occur, severe photoinhibition and metabolic limitation to photosynthesis may prevent Mediterranean sclerophylls to take advantage of higher atmospheric CO2, and may slow down recovery after the end of the dry season. The most sensitive forest types consist in tree species which are, in the Mediterranean basin, at the southernmost limit of their distribution range. In contrast, thermophilous trees are expected to have a greater diffusion both in southern and central Europe, as winter cold stress will be reduced by warming. Yet due to great variability of ecological features, the alleged substitution of tree species can follow a natural pattern from south to north and from low to high altitudes, without considering obstacles deriving from urbanization. For these reasons, research on the performance and ecologic plasticity of different genotypes, on species selection, and on planting and management techniques can have strategic importance for adaptive forest management.
Keywords: Drought stress; Global warming; Ozone; photosynthesis; UV radiation; Vegetation shift

Equilibrium of vegetation and climate at the European rear edge. A reference for climate change planning in mountainous Mediterranean regions. - Ruiz-Labourdette, Diego; Martínez, Felipe; Martín-López, Berta; Montes, Carlos; Pineda, Francisco D (International journal of biometeorology, 2011)
Mediterranean mountains harbour some of Europe's highest floristic richness. This is accounted for largely by the mesoclimatic variety in these areas, along with the co-occurrence of a small area of Eurosiberian, Boreal and Mediterranean species, and those of Tertiary Subtropical origin. Throughout the twenty-first century, we are likely to witness a climate change-related modification of the biogeographic scenario in these mountains, and there is therefore a need for accurate climate regionalisations to serve as a reference of the abundance and distribution of species and communities, particularly those of a relictic nature. This paper presents an objective mapping method focussing on climate regions in a mountain range. The procedure was tested in the Cordillera Central Mountains of the Iberian Peninsula, in the western Mediterranean, one of the ranges occupying the largest area of the Mediterranean Basin. This regionalisation is based upon multivariate analyses and upon detailed cartography employing 27 climatic variables. We used spatial interpolation of data based on geographic information. We detected high climatic diversity in the mountain range studied. We identified 13 climatic regions, all of which form a varying mosaic throughout the annual temperature and rainfall cycle. This heterogeneity results from two geographically opposed gradients. The first one is the Mediterranean-Euro-Siberian variation of the mountain range. The second gradient involves the degree of oceanicity, which is negatively related to distance from the Atlantic Ocean. The existing correlation between the climatic regions detected and the flora existing therein enables the results to be situated within the projected trends of global warming, and their biogeographic and ecological consequences to be analysed.
Keywords: climate; Cordillera Central Mountains of the Iberian Penins; Geographic factors; Global warming; Mediterranean flora; Multivariate regression with climatic data

Biogenic volatile organic compounds in the Earth system - Laothawornkitkul, Jullada; Taylor, Jane E; Paul, Nigel D; Hewitt, C Nicholas (New Phytologist, 2009)
Contents * Summary 27 * I. Introduction 27 * II. Regulation of BVOC emission 30 * III. Roles of BVOCs in the Earth system 32 * IV. BVOCs in a changing global environment 36 * V. Synthesis 44 * Acknowledgements 44 * References 44 Summary Biogenic volatile organic compounds produced by plants are involved in plant growth, development, reproduction and defence. They also function as communication media within plant communities, between plants and between plants and insects. Because of the high chemical reactivity of many of these compounds, coupled with their large mass emission rates from vegetation into the atmosphere, they have significant effects on the chemical composition and physical characteristics of the atmosphere. Hence, biogenic volatile organic compounds mediate the relationship between the biosphere and the atmosphere. Alteration of this relationship by anthropogenically driven changes to the environment, including global climate change, may perturb these interactions and may lead to adverse and hard-to-predict consequences for the Earth system.
Keywords: atmospheric chemistry; biogenic volatile organic compounds (BVOCs); climate change; Global warming; plant defence; plant volatiles; tritrophic interaction

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V; Castro-Diez, P; Valladares, F (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V.; Castro-Díez, P.; Valladares, F. (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Forest pathogens with higher damage potential due to climate change in Europe - La Porta, N; Capretti, P; Thomsen, I M; Kasanen, R; Hietala, A M; Von Weissenberg, K (Canadian Journal of Plant Pathology, 2008)
Abstract Most atmospheric scientists agree that climate changes are going to increase the mean temperature in Europe with increased frequency of climatic extremes, such as drought, floods, and storms. Under such conditions, there is high probability that forests will be subject to increased frequency and intensity of stress due to climatic extremes. Therefore, impacts of climate change on forest health should be carefully evaluated. Given these assumptions, several fungal diseases on trees may become more devastating because of the following factors: (i) abiotic stresses, such as drought and flooding, are known to predispose trees to several pathogens; (ii) temperature and moisture affect pathogen sporulation and dispersal, and changes in climatic conditions are likely to favour certain pathogens; (iii) migration of pathogens triggered by climatic change may increase disease incidence or geographical range, when pathogens encounter new hosts and (or) new potential vectors; and (iv) new threats may appear either because of a change in tree species composition or because of invasive species. If infection success is dependent on temperature, higher mean temperatures may lead to more attacks. Pathogens that have been of importance in southern Europe may spread northward and also upward to mountains. Pathogens with evolutionary potential for greater damage should be identified to estimate the magnitude of the threat and to prepare for the changing conditions. A review of the above-mentioned cases is presented. Some priorities to improve the ability to predict impacts of climate change on tree diseases are discussed.
doi: 10.1080/07060661.2008.10540534
Keywords: Drought; epidemiology; forest diseases; Global change; Global warming; opportunistic fungi; pathogenic fungi; predisposition; review; Temperature; water stress

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C. M.; SCOTT, J. K. (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C M; SCOTT, J K (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease